The impact of digital marketing on the business performance of business individuals in Ho Chi Minh City - Lê Thị Tuyết Thanh; Lê Thị Khánh Tường; Trần Thanh Nam (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2022)
Research and analyze the impact of digital marketing tools on the business performance of business individuals in Ho Chi Minh City. Through a survey of 340 business individuals using digital marketing tools in Ho Chi Minh City. The results of Exploratory Factor Analysis (EFA) have shown four factors affecting the business performance of business individuals, which are: social media, search engine optimization, Web/Blog, and display advertising. Multivariate regression results show that display advertising has the strongest influence on the business performance of business individuals. Research results provide useful information to help businesses allocate reasonable budgets as well as fully exploit digital marketing tools to improve business efficiency.